Manajemen Kurikulum dalam Meningkatkan Mutu Pendidikan di MTs. Muallimin Muallimat Bahrul Ulum Tambakberas Jombang - Ilham Ula Aghna; Didin Sirojudin (ISLAMIKA, 2023)
The quality of education will not be able to increase if the components of the curriculum management section are not established as the basis for the educational process. Educational institutions can improve the quality of education by implementing curriculum management. This study aims to understand curriculum management to improve the quality of education at Mts. Muallimin Muallimat. This study uses a quantitative descriptive methodology, collecting data through observation, interviews, and documentation, and analyzing the data through collection, data reduction, data presentation, drawing conclusions, and data verification.The results of this study indicate that curriculum management at Mts. Muallimin Muallimat, that is (1) planning involving school supervisors, existing stakeholders, and all teacher councils participating in the preparation of madrasah curriculum planning. (2) the implementation is adjusted to the curriculum planning that has been agreed upon from the various elements concerned so that the implementation is effective and efficient. (3) evaluation with the mechanism of educators and stockholders attending meetings where they expressed constraints and criticisms and advice on curriculum planning and implementation and following up on improvements in curriculum planning for the new academic year. Based on the findings of the study, it can be concluded that of madrasah curriculum management is to improve the quality of education and to foster stronger relationships between all participating madrasah organizations so that the vision, mission and goals of educational institutions can be carried out effectively and efficiently.